Perancangan Sistem Informasi Berbasis Website Pada UMKM Vina Kasur - Fitrah Ramadhani; Dhea Tri Indah Zebua; Naghea Zuella; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
In the digital era, the ability of MSMEs to keep up with technological developments and utilize them effectively is very important. Web design-based learning projects for MSMEs are an important effort to overcome this problem. With a focus on a practical learning approach, this project aims to empower MSMEs to design and manage websites that suit their business needs. The interview method is a way to collect data, through direct interviews with Vina Kasur. Then the answers from the interview results were summarized by the researcher. With a successful launch, we will see a positive impact with a significant increase in the number of customers and sales volume. Through the website creation project for MSMEs, we succeeded in applying the basic concepts acquired during the learning process. The process of analysis, website structure planning, and functionality development has formed a solid foundation for this project. The result is a website for MSME Vina Kasur that not only increases the business's online presence but also provides a better experience.